A critical Analysis of social distancing as a policy to combat the Spread of Corona Virus in Zimbabwe - Samutereko, Edmond Z. (Technium Social Sciences Journal, 2021)
This paper critically analyses the social distancing policy adopted by many nations in the fight against Covid 19 delimiting it in the context of Zimbabwe. The concept of social distancing as a method to combat the spread of the virus in defined. The epidemiology of the disease is outlined to have an appreciation of why social distance is highly recommended during corona virus pandemic as declared by the World Health Organisation in March 2020. The application of the methods of the social distancing may be applicable to certain contexts and may not be applicable in other places. This will be assessed with reference to Zimbabwe where some of the facilities are not conducive for quarantine, isolation and lockdown. Issues of poverty, economy, social amenities and basic needs are some of the factors for consideration for social distancing and lockdown. Possible recommendations shall be given so that the country may be ready to fight the pandemics of such kind in future. For example adequate and clear guidance may be needed especially for semi- formal and informal businesses so as to protect the most vulnerable and also alternative methods be applied on schools and religious gatherings other than closures. The Government as a policy maker and enforcer need to be pro -active in the fight of the pandemic so that the implementation of lockdown and social distancing is not just mere wastage of time since the outbreak will strike regardless of that policy.